1994
DOI: 10.1002/gcc.2870100306
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of loss of heterozygosity at 11 p with tumour progression and survival in non‐small cell lung cancer

Abstract: Loss of heterozygosity (LOH) affecting loci at 11p13 and 11p15 occurs in childhood and adult carcinomas, including non-small cell lung cancer (NSCLC). In NSCLC, the highest reported frequency of LOH was 72% at the 11p13 catalase (CAT) locus. As this locus is centromeric to the Wilms' tumour (WT1) locus, possible involvement of WT1 in the pathogenesis of NSCLC was considered. We thus examined 101 cases of NSCLC for LOH at the WT1 and five other polymorphic loci along 11p. At 11p13, the frequencies of LOH were 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…Traditionally, this involves polymerase chain reaction (PCR)-based amplification of simple sequence length polymorphisms (SSLPs) and the analysis of the amplified products using either gel-or capillary-based electrophoresis. Many studies in lung cancer have focused on LOH analyses in specific regions of the genome and correlated these findings with clinical outcome parameters including survival (Fong et al, 1994(Fong et al, , 1995Mitsudomi et al, 1996;Tseng et al, 1999). However, given the genetic complexity of lung cancers, LOH events from multiple loci likely contribute to the overall phenotype of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, this involves polymerase chain reaction (PCR)-based amplification of simple sequence length polymorphisms (SSLPs) and the analysis of the amplified products using either gel-or capillary-based electrophoresis. Many studies in lung cancer have focused on LOH analyses in specific regions of the genome and correlated these findings with clinical outcome parameters including survival (Fong et al, 1994(Fong et al, , 1995Mitsudomi et al, 1996;Tseng et al, 1999). However, given the genetic complexity of lung cancers, LOH events from multiple loci likely contribute to the overall phenotype of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…The minimal region of LOH was 650 kb and¯anked by the markers D11S988 (centromeric) and D11S860 (telomeric). Numerous investigators have reported LOH in this region for non-SCLC with frequencies ranging from 17% to 82% (Bepler and Garcia-Blanco, 1994;Fong et al, 1994;Ludwig et al, 1991;Shiraishi et al, 1987;Skinner et al, 1990;Tran and Newsham, 1996;Weston et al, 1989). LOH in or near this region has also been described for breast, ovarian, esophageal, stomach, and other cancers arising in adults (Ali et al, 1987;Fearon et al, 1985;Karnik et al, 1998;Lu et al, 1997;Ranzani et al, 1993;Shibagaki et al, 1994;Tran and Newsham, 1996;Viel et al, 1992;Winqvist et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…TSG101 was localized to chromosome 11p15 (Li et al, 1997), a region frequently lost in several human tumor types including breast cancer (Winqvist et al, 1995;Gudmundsson et al, 1995) and NSCLC (Sundareshan and Augustus, 1996;Fong et al, 1994;Bepler et al, 1994;Izuka et al, 1995). It has been suggested that the 11p allele loss is associated with disease progression in NSCLC (Fong et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the 11p allele loss is associated with disease progression in NSCLC (Fong et al, 1994). While the normal function of TSG101 is unknown, several structural motifs have been identi®ed including a proline-rich region and a predicted coiled-coil domain nearly identical to that of its murine homolog.…”
Section: Introductionmentioning
confidence: 99%